Iron-folic acid adherence and associated factors among pregnant women attending antenatal care at Metema District, Northwest Ethiopia - Yismaw, Ayenew Engida; Tulu, Helen Bekele; Kassie, Fisseha Yetwale; Araya, Bilen Mekonnen (Frontiers in Public Health, 2022)
Abstract Background: At least half of anemia worldwide is due to iron deficiency. Iron and folate supplementation can effectively control and prevent anemia during pregnancy. Despite the efforts to reduce iron deficiency anemia during pregnancy, only few women took an iron supplement as recommended. This study investigated the factors associated with adherence to iron-folic acid supplementation. Methods: An institution based cross sectional study was carried out from April, 1- May30, 2021 among women attending ANC clinic at Metema district governmental health institutions. Data were collected by face to face interview with interview administered questionnaire. Epi info version 7.1 and SPSS 20 were used for data entry and analysis, respectively. Significant association were identified on the basis of the adjusted odds ratio (AOR), with 95% confidence, and p-value <0.05. Results: The proportion of women adhering to iron-folic acid was found to be 34.9% with (95% CI: 31, 38.8%). Maternal educational status (AOR=6.09,95% CI(3.26,11.4)), time of registration (AOR=1.95,95% CI(1.25,3.06)),knowledge of Iron and folic acid supplementation (AOR=2.80, 95% CI(1.83,4.28)), knowledge of anemia (AOR=1.61,95% CI(1.06,2.43)) and history of anemia during current pregnancy (AOR=2.31,95% CI(1.36,3.94)) were found to be factors significantly associated with adherence to iron-folic acid supplementation . Conclusions: Adherence of iron-folate supplementation was low in the study area. Increasing maternal awareness, informing them about the benefits of iron-folate supplements, and early registration to ANC were determinants to increase iron-folic acid adherence. Keywords: Iron-folic acid, pregnant women, Adherence, Anemia, Metema.